Real-world, in-clinic challenges and opportunities in the management of heart failure patients with dyslipidaemia: comprehensive experiences by healthcare professionals - Khobragade, Kunal; Kumar, Neeraj (International Journal of Research in Medical Sciences, 2025)
Background: Dyslipidemia is a significant modifiable risk factor for cardiovascular disease (CVD), particularly in Asian Indians, who exhibit a distinctive lipid profile. Effective management is critical in heart failure (HF) patients to mitigate CVD risk. Methods: This cross-sectional, observational study, the Dyslipidemia and Heart Failure Survey, was conducted across India from July to September 2023. It involved 325 healthcare professionals (HCPs) specializing in HF management. Data were collected using a structured questionnaire addressing lipid parameter assessment, ARNi (sacubitril/valsartan) therapy and its integration into HF management. Results: Among the HCPs, 49% emphasized addressing all lipid parameters, including HDL, LDL, triglycerides and non-HDL, with LDL cholesterol identified as the primary therapeutic target. Statins were the most commonly prescribed lipid-lowering agents. For de novo heart failure with reduced ejection fraction (HFrEF) patients, 55% of HCPs preferred ARNi over ACE inhibitors or ARBs. However, HCP practices vary widely regarding adherence to ACC/AHA guidelines for stage C HFrEF, with 145 (45%) fully compliant and 136 (42%) selectively advising ARNi for specific subsets. Barriers to ARNi usage included concerns about hyperkalemia and angioedema. Despite these challenges, many HCPs expressed optimism about ARNi's potential to improve ejection fraction, underscoring the need for a tailored, patient-specific approach to its application. Conclusions: The study highlights current practices and challenges in managing dyslipidemia and HF among Indian HCPs. It represents the need for improved adoption of ARNi therapy and targeted interventions to address barriers, paving the way for better outcomes in HF management.